Expanding the toolbox of photon upconversion for emerging frontier applications. Issue 4 (27th January 2022) - Huang, Jinshu; Yan, Long; Liu, Songbin; Tao, Lili; Zhou, Bo
Abstract : This review summarizes the recent progress on lanthanide-based upconversion materials, focusing on the emerging approaches to the smart control of upconversion, and their frontier applications. Abstract : Photon upconversion in lanthanide-based materials has recently shown compelling advantages in a wide range of fields due to their exceptional anti-Stokes luminescence performances and physicochemical properties. In particular, the latest breakthroughs in the optical manipulation of photon upconversion, such as the precise tuning of switchable emission profiles and lifetimes, open up new opportunities for diverse frontier applications from biological imaging to therapy, nanophotonics and three-dimensional displays. A summary and discussion on the recent progress can provide new insights into the fundamental understanding of luminescence mechanisms and also help to inspire new upconversion concepts and promote their frontier applications. Herein, we present a review on the state-of-the-art progress of lanthanide-based upconversion materials, focusing on the newly emerging approaches to the smart control of upconversion in aspects of light intensity, colors, and lifetimes, as well as new concepts. The emerging scientific and technological discoveries based on the well-designed upconversion materials are highlighted and discussed, along with the challenges and future perspectives. This review will contribute to the understanding of the fundamental research of photon upconversion and further promote the development of new classes of efficient upconversion materials towards diversities of frontier applications in the future.